Oral health research: A source for innovative new statistical developments. (December 2014) - Lesaffre, Emmanuel; Declerck, Dominique
This article reviews the challenges and opportunities that oral health research may offer to a statistician. To illustrate this, we focus on the Signal Tandmobiel® study, a longitudinal oral health survey that triggered many statistical explorations and developments over the last two decades. For example, non-standard distributions are more the rule than the exception in oral health research. In addition, often measurement error problems need to be addressed. The hierarchical structure of the oral health data also poses non-standard challenges. For instance, caries experience in the mouth is spatially correlated with, however, a specific metric defining the distance between two occurrences. In addition, since caries experience in the context of an epidemiological study is only measured at intervals, analysis of survival involves interval-censoring. Finally, when analyzing a realistic data set in oral health, all the above issues may have to be dealt with simultaneously.